THE USE OF DIGITAL INNOVATIONS IN THE DEVELOPMENT OF THE ARCTIC. Issue 1 (July 2021) - Dyatlov, S A; Didenko, N I; Abakumova, M V; Kulik, S V
Abstract: The paper describes the application of Industry 4.0 technologies, gives an overview of previous research on digital innovations, and defines goals and objectives of the research. The core concept of «Industry 4.0 technology» and features of the ways to exploit it in the Arctic institutions have been examined. There has been carried out an analysis of international practices to apply Industry 4.0 technologies in all spheres of life. The flexible automated production of goods or services based on new generation robotics and factories in the Arctic zone has been considered as being the highest stage of complex automated production. An example of automated use of products and services are «smart houses», or «smart things». Methods of collection of advanced production technologies have been discussed. A strategy has been developed to select the most advanced production technologies for spheres of life and the best possible strategic option has been defined. Financial and time resources were chosen as optimization criteria.